Metal‐Based Compounds as Prospective Antileishmanial Agents: Inhibition of Trypanothione Reductase by Selected Gold Complexes. Issue 10 (23rd August 2013) - Colotti, Gianni; Ilari, Andrea; Fiorillo, Annarita; Baiocco, Paola; Cinellu, Maria Agostina; Maiore, Laura; Scaletti, Federica; Gabbiani, Chiara; Messori, Luigi
<x xml:space="preserve">Abstract</x> Picking a fight with parasites! Trypanothione reductase (TR) is a validated drug target for the development of antileishmanial agents. A group of structurally diverse gold‐containing compounds was evaluated in vitro for TR inhibition. A number of compounds exhibited potent activity and deserve further pharmacological evaluation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>